2017
DOI: 10.18240/ijo.2017.04.07
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of gypenosides in experimental autoimmune optic neuritis

Abstract: Treatment with gypenosides exerts protective effects on retinal nerve fibers and axons in EAON. When combined with gypenosides, methylprednisolone reduces demyelination in the acute stage of EAON.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…However, previous studies assessing optic nerve and retinal pathology in autoimmune ON reported little to no difference between the CFA-only group and healthy controls in inflammatory pathology and neuro-axonal degeneration [2, 57]. Our results suggests that IRL changes in EAE are primarily influenced by pRNFL changes over time; yet previous OCT studies investigating pRNFL changes in EAE mice report contradictory findings [3, 32]. This may be due to the use of different species and immunisation protocols, but also because of methodological limitations as the pRNFL is a relatively thin structure in rodents and thus difficult to segment accurately on its own.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…However, previous studies assessing optic nerve and retinal pathology in autoimmune ON reported little to no difference between the CFA-only group and healthy controls in inflammatory pathology and neuro-axonal degeneration [2, 57]. Our results suggests that IRL changes in EAE are primarily influenced by pRNFL changes over time; yet previous OCT studies investigating pRNFL changes in EAE mice report contradictory findings [3, 32]. This may be due to the use of different species and immunisation protocols, but also because of methodological limitations as the pRNFL is a relatively thin structure in rodents and thus difficult to segment accurately on its own.…”
Section: Discussioncontrasting
confidence: 60%
“…Several studies have assessed retinal pathology using OCT in experimental models of ON [3, 11, 16, 2832]. In particular, studies have revealed initial phases of IRL thickening [11, 31] around the optic nerve head (ONH) followed by severe thinning at later stages of the disease in EAE mice compared to healthy controls [16].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with Gp exerted protective effects on retinal nerve fibers and axons. These results strongly indicate that the Gp might be a useful supplement for optic neuritis treatment (Zhang et al 2017).…”
Section: Discussionmentioning
confidence: 57%
“…Mice were placed on a platform after anaesthesia and pupil dilation and adjusted to ensure that the incident beam was perpendicular to the central cornea and passed through the pupil. The retinal thickness of mice at a circle with a diameter of 3.45 mm (system setting) using the optic disc as the centre was measured by OCT with a 25D lens (50744, Heidelberg, Germany) 45 . After the measurement of live animals, the mice were anaesthetised and cardiac perfused with 4% paraformaldehyde in phosphate buffer.…”
Section: Methodsmentioning
confidence: 99%